MECHANISMS OF YOUTH POLICY FORMATION AT THE INTERNATIONAL LEVEL - Baglyk V.S. (Pressing Problems of Public Administration, 2015)
The article analyzes the main directions of realization of the state youth policy. Considers international legal documents regulating areas of youth policy in various fields of social development. The conclusions about the use of foreign experience of state youth policy.